Indian Ocean Resources and Technology. - Roonwal, Ganpat Singh (Milton : CRC Press, 2017)
"The current scenario provides an ideal opportunity to confer higher priority to the marine resources of the Indian Ocean, particularly in terms of integrated management of the deep sea, shallow sea and coastal resources. This will maximize their potential in the sustainable development goal (SDG) pattern, leading to an appropriate environmental management. Therefore, this book aims to provide an overview of the area and to highlight the potential market opportunities represented by this vast and rapidly developing nation. In doing so the following aspects have been covered:Exclusive title focussing on mineral resources of Indian ocean.Discusses living, nonliving, ocean waves and tidal energy, ocean environment and protection aspects.Includes information on key themes, details of organizations associated with the Indian Ocean.Illustrates deep sea mining technology and environmental perspectives.Covers hydrocarbons-sub sea oil and gas, minerals from placer deposits to deep sea nodules, sea floor massive sulphides and cobalt rich encrustations."--Provided by publisher.
""3.3 Processes of Accretion and Formation """"3.4 Crust Texture: Thickness, Rates of Growth, and Substrate Characteristics ""; ""3.5 Indian Ocean Occurrences ""; ""References ""; ""4. Ores in the Deep Sea: Seafloor Massive Sulfides and Metalliferous Mud ""; ""4.1 Introduction ""
""4.2 Nature, Distribution, and Origin of SMS Deposits and Metalliferous Mud ""
OCLC-licensed vendor bibliographic record.